Primary replacement for the management of exposed orbital implant. (2nd November 2019) - Curragh, David S.; Kamalarajah, Srikandan; Lacey, Brendan; White, Stephen T.; McNab, Alan A.; Kalantzis, George; Dolman, Peter J.; Selva, Dinesh; Rajak, Saul N.
ABSTRACT: Purpose : We present a series of primary orbital implant replacement for cases of implant exposure to describe our experience of this one-staged surgical approach. Methods : This study reports on a one-stage technique which involved the removal of the exposed implant or dermis fat graft (DFG) and insertion of a secondary (replacement) in the same procedure, with a variety of materials, including autologous tissue. Re-exposure in a socket where a DFG was placed was defined as a new defect in the newly epithelialized conjunctiva or dehiscence of the dermis-conjunctiva junction. All cases of primary replacement for the management of exposed orbital implant, porous and non-porous, were included, even when there were clinical signs suggestive of infection. The primary outcome was the rate of re-exposure, requiring additional surgical procedures. Infection following primary replacement was a secondary outcome. Results : Seventy-eight patients had primary replacement for the management of an exposed orbital implant. 6.4% had re-exposure at a mean follow-up of 49.7 months (9.1% for ball implants and 4.5% for DFG). The rate of exposure was higher in those with prior signs of infection than those without (8% vs. 3.6%). Re-exposure occurred in 4.5% of cases with DFG implantation, 4.3% of cases with non-porous implants and in 20% of cases with porous implants. Conclusion : Primary replacement for management of exposed orbital implant, porous and non-porous, has a high rate of successful outcome even in cases with presumed or confirmed infection.